2010
DOI: 10.1016/j.neuron.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptors Activated by Subventricular Zone Astrocytic Glutamate Are Critical for Neuroblast Survival Prior to Entering a Synaptic Network

Abstract: SUMMARY Even before integrating into existing circuitry, adult-born neurons express receptors for neurotransmitters, but the intercellular mechanisms and their impact on neurogenesis remain largely unexplored. Here, we show that neuroblasts born in the postnatal subventricular zone (SVZ) acquire NMDA receptors (NMDARs) during their migration to the olfactory bulb. Along their route, neuroblasts are ensheathed by astrocyte-like cells expressing vesicular glutamate release machinery. Increasing calcium in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
220
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(236 citation statements)
references
References 57 publications
12
220
0
4
Order By: Relevance
“…2 we did not find any difference in neuroblast migration rate either with DNQX/APV nor NPS2390 antagonists. These results are in agreement with previous studies showing that NMDA and metabotropic glutamate receptors are not involved in RMS neuroblast migration (Platel et al, 2008b;Platel et al, 2010). However while Platel et al (2008) show increase speed rate following inhibition of Glu K5 -containing kainate receptors we did not find any regulation on neuroblast migration by DNQX/APV antagonists.…”
Section: Amino Acids: Gaba and Glutamatesupporting
confidence: 93%
“…2 we did not find any difference in neuroblast migration rate either with DNQX/APV nor NPS2390 antagonists. These results are in agreement with previous studies showing that NMDA and metabotropic glutamate receptors are not involved in RMS neuroblast migration (Platel et al, 2008b;Platel et al, 2010). However while Platel et al (2008) show increase speed rate following inhibition of Glu K5 -containing kainate receptors we did not find any regulation on neuroblast migration by DNQX/APV antagonists.…”
Section: Amino Acids: Gaba and Glutamatesupporting
confidence: 93%
“…Approximately one-third of adult-born GCs ⌬GluN2B died before differentiation in the OB begins. It is likely that this subpopulation coincides with the one described by Platel et al (2010). These authors investigated the effect of GluN1 deletion in GCs, and found that the manipulation did not affect direction and speed of migration, but eventually resulted in the demise of a similar fraction of GCs in the RMS.…”
Section: Discussionmentioning
confidence: 90%
“…NMDARs are hetero-oligomers that contain the obligatory GluN1 subunit and variable GluN2 subunits. Upon deletion of GluN1 (⌬GluN1), the majority of adult-born GCs complete migration (Platel et al, 2010), but eventually die during synaptic development (Lin et al, 2010). Similarly, ⌬GluN1 neurons in the adult dentate gyrus die during differentiation (Tashiro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Néanmoins nos études précédentes démontraient la présence et la fonctionnalité d'autres récepteurs au glutamate durant la migration rostrale [3]. Nous avons donc entrepris de caractériser plus en détails l'apparition des récepteurs NMDA, la source du glutamate qui les active ainsi que le rôle de ces récepteurs en utilisant la technique knock-out sur cellule unique in vivo [4].Expression des récepteurs NMDA sur les neuroblastes émergeant de la ZSV Nous avons tout d'abord analysé l'expression des récepteurs NMDA lors de la phase de migration/maturation des neuroblastes dans la ZSV et la VMR. Nous avons pour cela utilisé deux techniques, l'électrophysiologie et l'imagerie calcique, que nous avons appliquées à des tranches de cerveau.…”
unclassified
“…Néanmoins nos études précédentes démontraient la présence et la fonctionnalité d'autres récepteurs au glutamate durant la migration rostrale [3]. Nous avons donc entrepris de caractériser plus en détails l'apparition des récepteurs NMDA, la source du glutamate qui les active ainsi que le rôle de ces récepteurs en utilisant la technique knock-out sur cellule unique in vivo [4].…”
unclassified